The semantics of derivatives, formed of the names of colors (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The modern Ukrainian language is rich in coloratives and their derivatives. The author presents the classification of structural-semantic groups of derivatives, formed from the names of colors. In its basis there are lexical meaning of words and the way of their word-formation. The material demonstrates inexhaustible possibilities of word-formation in the Ukrainian.language.
Keywords: derivative words; coloratives; affixes; suffixes; productive words; way of word-formation